Control of selectivity in methane conversion reactions in RF plasma: the influence of reaction conditions - Jeon, Byungwook; Park, Eun Duck; Kim, Yu Kwon (Research on Chemical Intermediates, 2018)
RF plasma excitation of methane has been studied in an effort to optimize the reaction conditions for a selective partial oxidation of methane. The reaction products of RF-excited methane are C2 hydrocarbons such as ethane and acetylene when O2 is not used. The introduction of a few percent of O2, however, is found to switch the selectivity in favor of CO while CO2 formation is suppressed down to a level below a few percent. Interestingly, in the low O2 ratio regime (0–0.6), the selectivity between CO and C2 hydrocarbons is observed to vary systematically in response to the detailed reaction conditions, including flow rate, pressure and applied RF power, which are explained by the competition between coupling and partial oxidation reactions. Variation in the density and the residence time of the active species in the plasma is suggested to determine the overall reaction pathways. The present results suggest a possibility of a selective production of the partial oxidation products of methane such as CO with a high selectivity and a high conversion efficiency using controlled RF plasma from methane and O2.
Keywords: High conversion efficiency; Partial oxidation products; Partial oxidation reactions; Partial oxidations; Plasma excitation; RF plasma; Selective partial oxidation; Selective production; Acetylene; Carbon monoxide; Methane; Partial oxidation; Plasma excitation; RF plasma